The Coefficient of the Whole Is an Average of the Coefficients of Its Parts : A Special Case of Restricted Least Squares - Kee, Hiau Looi (2012)
This paper provides a consistent estimate of the bound of the marginal effect of an unobserved right-hand side variable on the dependent variable when only the sum of that variable with a positively correlated variable is available.